Understanding the Needs of Ontario Educators in Supporting Students With Acquired Brain Injury in the Classroom. (2nd March 2021) - Stevens, Sara A.; Provvidenza, Christine; Zheng, Sally; Agnihotri, Sabrina; Hunt, Anne; Scratch, Shannon E.
Abstract: Background: When a child sustains an acquired brain injury (ABI), the impact extends to significant environments in their life, including school. Educator knowledge of ABI can influence a child's success with academic and social reintegration. An assessment of educator ABI knowledge was conducted to determine what information they require to support school reintegration. Methods: A mixed‐methods approach included a sampling of educators in a needs assessment survey and workshop. The survey determined levels of educator knowledge regarding ABI in the classroom, and the workshop scoped educator views in the development of a user‐driven ABI learning program to enrich their expertise. Results: Our sample reported being somewhat knowledgeable about ABI and the impact on students. There were no differences based on respondents' educational role. Teachers reported having minimal and inadequate supports for students following ABI during school transitions, feeling unprepared to assist students during these transitions, and that families also appeared unprepared for school reintegration following ABI. The workshop identified the need for a 2‐part educational course. Conclusions: Supportive school environments are essential for the reintegration of students following ABI. This study identified educators' needs for ABI knowledge and resources to support their existing expertise.